OTU-028 Benchmarking of activity, process and outcome of emergency admission for ulcerative colitis across english hospitals. (8th June 2018) - Shawihdi, Mustafa; Dodd, Susanna; Appelbe, Duncan; Dixon, Pete; Grainger, Ruth; Cummings, Fraser; Bloom, Stuart; Bodger, Keith
Abstract : Introduction: The UK IBD Registry aims to make information work better for patients, clinical teams and the NHS. As part of the benchmarking reports provided to participating Trusts, we have developed organisational level metrics from routinely collected hospital episode statistics (HES) data – working with front-line teams to iteratively develop reports with feedback on content and local face-validity. We report national-level findings and institutional variation in activity, process and outcome of emergency care for UC. Methods: Admitted patient care data for English hospitals were analysed, identifying all-cause admissions for patients with UC and constructing algorithms to identify emergency activity, track process and outcome for UC-specific emergency admissions (UC-Em-Ad ), including in-hospital death (I-H-D ) and emergency surgery (Em-Surg ), all-cause 30 day readmission (30D-RA ) and twelve month outcome. Reports containing 5 year national and local trends and cumulative 5 year performance were distributed to sites in Dec 2017. This analysis summarises selected data for 133 Trusts present in all fiscal years (11/12 to 15/16). Results: Nationally, there were 31, 371 UC-Em-Ad (2 65 799 bed days; median LoS 6 days; 22 809 patients; mean age 40 years; male 50%; additional coded co-morbidities in 23%) with 1451 Em-Surg (4.62%=crude surgery rate; mean age 44 years; male 56.1%), 324 I-H-D (1.03%=crude mortality rate; mean age 76 years; 67% had additional coded co-morbidities; only 16% of deaths were post-surgery), 4916 30D-RA (15.7%=crude readmission rate). At Trust level, mean (95% limits) for indirectly standardised rates were: I-H-D 1.03% (0.90%–1.15%), Em-Surg 4.79% (4.31%–5.27%), 30D-RA 15.55% (15.0%–16.1%). Few outliers were identified and none consistently over time, with no significant trends identified for volume-outcome relationships. Funnel plots and regression analyses will be presented. Conclusions: These data provide real-world insights into processes and outcomes of emergency care for UC across England in the last five years, with a series of metrics to support both national and local quality improvement efforts. Linkages between HES and local Registry data offers potential to validate, refine and extend these benchmarking metrics. Funding: Crohn's and Colitis UK.